The Interplay of Financial Availability, Herding Behavior, and Cryptocurrency Investment Experience Moderated by Government Policy: A Study from Indonesia - Jul Aidil Fadli; Toto Rusmanto; Yohannes Kurniawan; Yanthi Hutagaol-Martowidjojo (Qubahan Academic Journal)
This study investigates how financial availability and herding behavior influence the experience of investing in cryptocurrencies, with government policies serving as a moderating factor. This study involved 297 individuals who actively invest in cryptocurrencies in Indonesia.  A structural equation model with partial least squares (PLS-SEM) approach was used in this study. The results show that financial availability and government policy affect cryptocurrency investment experience. Meanwhile, government policies have been shown to strengthen the influence of herding behavior. The results also show that herding behavior has no direct effect on cryptocurrency investment experience. Similarly, there is no evidence that government policies can moderate the effect of financial availability on cryptocurrency investment experience. The results show the importance of assessing the financial availability of investors in their investment activities and highlight the importance of government policies to increase the convenience of investing.